Yellowstone Cougars : Ecology before and during Wolf Restoration - Ruth, Toni K. (Toni Karen), 1963-; Hornocker, Maurice G.; Buotte, Polly C. (Book collections on Project MUSE., 2019)
"Examines the effect of wolf restoration on cougar population in Yellowstone National Park. No other study has addressed theoretical and practical aspects of competition between large carnivores. A thorough examination of cougar ecology, how they interact and [are] influenced by wolves, how this knowledge informs management and conservation."--Provided by publisher